The Influence of Human Resources on Economic Development in Indonesia (Systematic Literature Review) - Nurpida, Lisna; Tussoleha Rony, Zahara (Dinasti Publisher, 2024)
An important task of the HR council is to help the association achieve its goals. To achieve the hierarchical goal of performing authoritative tasks proficiently and actually, techniques/procedures or HR boards are required. The existence of HR value in an association can be a significant resource in the organization that later in the future can be an ally of hierarchical progress. With the aim that the presence of HR value (HR) can determine human nature as a significant holder of employment in encouraging the association concerned. The contest that occurs will affect how the association works. This is due to the longing in each association to turn into an association that succeeds in terms of execution.